Analisis Sifat Fisik dan Kimia Tanah pada Lahan Sawah di Kecamatan Kotamobagu Utara - Josua F. Manullang; Sandra E. Pakasi; Joice M. Supit; Jelie V. Porong (COCOS, 2020)
ABSTRACTThe study aims to determine the status of physical and chemical properties of soil on paddy soilin Kotamobagu Utara district. This research was conducted in November 2019 to January 2020using a survey method and laboratorios analysis. Soil samples were taken at thirteen points at adepth of 0 to 20 cm. The parameters measured were soila texture (Kang Biaw Tjwan method),pH (pH meter), C-organic (Walkley and Black method), nitrogen (Kjedhal method), phosphorus(Bray I method) and Potassium (Bray method I). Research data analysis using descriptiveanalysis. The results showed that soil texture in the research sites is silty loam, the content oforganic matter is in the range 1,25 % to 2,50 %, the content of soil pH is in the range 6,8 to 7,0 ,the content of the element nitrogen is in the range of 0.11% to 0.22% , phosphorus content in therange of 18.34 ppm to 23,21 , and potassium element content is in the range of 22,21 ppm to30,21 ppm. The chemical properties of paddy soils in Kotamobagu Utara District is at textureclass of silty loam and chemical properties of paddy soil with each respective criteria neutral soilpH, C-organic low to moderate, Nitrogen low to moderate, Phosphorus moderate and Potassiummoderate. In general, the physical and chemical properties of soil in paddy fields in KotamobaguUtara District are included in the criteria suitable for paddy soil.Key Word: Physical properties, chemical properties, Paddy Fields